On the thermomagnetic analysis of Matuyama reversed basalt from Gembudo cave, Hyogo Prefecture, Japan - 堂面, 春雄 (山口大学教育学部, 1988)
Abstract Since 1927 as Matuyama discovered the natural remanent magnetization of Gembudo basalts towards the oposite direction to the present geomagnetic field (R-NRM), few rock/paleo magnetic studies had been carried out on the basalts in the Gembudo district. The present author has been studying paleo/rock magnetically on the basalt from the vicinity of Gembudo. In this paper, the data on the thermo magnetic (Js-T) analysis thus obtained up to the present time are shown. The Js-T curves presented here showed that the original Curie point of the specimens is rather low, however, the curves are irreversible even in vacuum of 10^<-3> torr. The present author also showed some other examples of Js-T analysis of the Matuyama Reversed basalts come from Japan and Iceland. Gembudo cave is a rocky cave showing well developed columnar joints of basaltic lava. Because of their beauty and marvel, this cave has been appointed one of the national monuments in Japan. Gembudo is situated in the northern Hyogo Prefecture, at about 110 km aparted from the City of Kyoto. And also this cave is the very site of the original spot at where the name ”Gembu-gan” in Japanese as for the English name ”Basalt” has been given to such the kind of rocks after the name ”Gembudo”. In early 1900s, Matuyama (1927) had firstly made his investigations so ingenious that the paleomagnetic study on the basaltic rocks taken from this cave, Gembudo and he found that those rock specimens showed the reversed natural remanent magnetization (R-NRM) . This discovery made finally his name eternal and glorious in the Earth Sciece World as ”Matuyama Reversed Epoch” of the geomagnetic history. In this district, there are a few of such rocky caves near by Gembudo. This time, the thermo